Incidence of Perimenopausal Syndrome in Chinese Women Aged 40 to 65 Years: a Meta-analysis - JIA Yu, ZHOU Zitong, CAO Xuehua, HU Wanqin, XIANG Feng, XIONG Langyu, WANG Xiaoxia (Zhongguo quanke yixue, 2023)
Background With the rapid development of economy and society in China, the living standards and health care awareness have been improved significantly, the average life expectancy of our population is gradually prolonged, causing increasing population of perimenopausal women, therefore, the health management of perimenopausal women has become more important. Perimenopausal syndrome can be seen in women aged 40-65 years, which can seriously affect the physical and mental health and quality of life of patients. Objective To systematically review the incidence of perimenopausal syndrome in Chinese women aged 40-65 years. Methods PubMed, Embase, Web of Science, CNKI, Wanfang Data, CBM and VIP were searched by computer to collect cross-sectional studies on the occurrence of perimenopausal syndrome in Chinese women aged 40-65 years from inception to February 1, 2023. Two investigators independently screened the literature, extracted data and evaluated the quality of included literature. Meta-analysis was performed using Stata 17.0 software. Results A total of 62 cross-sectional studies were included, with a total sample size of 82 340 cases. Meta-analysis showed that the incidence of perimenopausal syndrome in Chinese women aged 40-65 years was 61.0%. The results of subgroup analysis showed that the incidence of perimenopausal syndrome in women aged 40-45 years, >45-50 years, >50-55 years, >55-60 years and >60 years was 42.6%, 53.8%, 64.6%, 59.7% and 56.1%, respectively. The incidence of perimenopausal syndrome in women aged 40-65 years with normal, disordered and postmenopausal menstrual status was 43.6%, 56.9% and 61.3%, respectively. The incidence of perimenopausal syndrome in women aged 40-65 years with and without chronic diseases was 85.9% and 68.3%, respectively. The incidence of perimenopausal syndrome was highest in women aged 40-65 years in Southwest China at 71.3%, and at 57.4%, 57.9%, 50.5%, 59.2%, 69.5%, and 68.6% in North, East, South, Northwest, Northeast, and Central China, respectively. The incidence of perimenopausal syndrome in women aged 40-65 years with education level of junior high school and below, high school or technical secondary school, university and above was 54.1%, 55.7% and 49.6%, respectively. The incidence of perimenopausal syndrome in Han Chinese and ethnic minority women aged 40-65 years was 62.1% and 64.7%, respectively. Conclusion The incidence of perimenopausal syndrome is high in women aged 40 to 65 years in China. Among them, women aged >50-55 years, menopausal, suffering from chronic diseases, living in southwest region, with education level of high school or below, and ethnic minorities are at high risk of perimenopausal syndrome. We should pay attention to the prevention, screening and intervention of perimenopausal syndrome in relevant population to lay the foundation of elderly health in women.